Implementación de un sistema web para mejorar la gestión de proyectos de servicios generales de la empresa stecser srl - Ocon Peredo, Nohelia Brenndha (2017)
The present project called "IMPLEMENTATION OF A WEB SYSTEM TO IMPROVE THE MANAGEMENT OF PROJECTS OF GENERAL SERVICES OF THE STECSER S.RL.", aims to improve the management of projects of the different works carried out by the company, elaborating a proposal of Information system solution for the attention of your current processes; And provide information availability, ease of use of the software and better performance of users; Reflected in the decrease of time in the registration of information of projects, in the increase of the satisfaction of the user, in the reduction of times of the generation of Reports of Management and in the reduction of costs. We start from the description of the organization in all its areas, considering an analysis of its critical factors of success, as well as the SWOT analysis, among others. It describes the main processes that occur within the organization, as well as their representation through diagrams. It also specifies its main objectives as a company, its goals and everything concerning its business philosophy. The achievement to develop software is to provide a better competitive tool, relevant, accurate and timely for the integration of the departments of the enterprise. Through our acquired and implemented in the present work we project knowledge in the short term, provide better solutions regarding the management of information, giving a competitive advantage to the company and concluded satisfactorily in the objectives.